A catalyst applied to low water / oil ratio conditions, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611489306.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0045]1、本发明通过对球形催化剂活性粉末配方、整体配方以及涂覆成型工艺的开发,得到了适用于低水烯比条件的高选择性、高强度球形催化剂产品,结合对进料比例的控制,催化剂在低水烯比条件下性能优秀,床层热点温度低,满足工业使用需求,其中实施例1~8在0.3的水烯比下均能达到93%以上的丙烯醛与丙烯酸总收率,热点温度均低于410℃,磨耗均合格。
Smart Images

Figure CN122974342A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation technology, specifically to a catalyst for use under low water-to-olefin ratio conditions, its preparation method, and its application. Background Technology
[0002] Industrially, acrylic acid is produced through a two-step oxidation process of propylene. In the first step, propylene is oxidized to acrolein, and in the second step, it is oxidized to acrylic acid. The product gas from both reactions undergoes rapid cooling absorption, azeotropic distillation for dehydration, extraction and solvent recovery, and removal of heavy components to obtain refined acrylic acid. Azeotropic distillation is the core separation stage. After the crude product is fed into the azeotropic distillation column, toluene or methyl isobutyl ketone is added as an azeotropic agent. Water and the azeotropic agent are distilled off from the top of the column, and dehydrated crude acrylic acid is obtained from the bottom. During the azeotropic distillation stage, the crude product remains in the high-temperature bottom of the column for an extended period, resulting in extremely high energy consumption, accounting for approximately one-third of the plant's total steam consumption. Furthermore, acrylic acid readily polymerizes within the column, requiring a large amount of polymerization inhibitors. Frequent blockage of the reboiler in the bottom of the column necessitates periodic shutdowns for cleaning. The azeotropic distillation stage significantly increases the production cost of acrylic acid, and the use of azeotropic agents such as toluene also creates environmental pressure. Therefore, production personnel hope to replace azeotropic distillation with a crystallization process. Energy consumption can be significantly reduced through crystallization processes. Replacing multiple pieces of equipment such as azeotropic towers, oil-water separators, and recovery towers with crystallizers and centrifuges can greatly shorten the equipment chain.
[0003] Crystallization processes have strict requirements on the water content of the crystallization feed, thus necessitating a reduction in the water content of the upstream oxidation reaction feedstock, i.e., the water-to-olefins ratio (water-to-olefins ratio). Typically, a water-to-olefins ratio below 0.5 results in a product composition suitable for crystallization separation. However, in currently disclosed technical solutions, the water-to-olefins ratio is usually higher than this value. For example, patent CN112958103B discloses an extruded catalyst for the catalytic oxidation of propylene to acrolein, in which the feed ratio of propylene, air, and water vapor is 10:75:15, i.e., a water-to-olefins ratio of 1.5. Patent CN101850259B discloses a sheet-forming catalyst for the oxidation of propylene to acrolein at high space velocity, wherein the water-to-olefins ratio in the embodiments is 1.5 or higher. Patent CN105195166A discloses a spherical coated catalyst for the oxidation of propylene to acrolein, in which the water-to-olefins ratio is 1.7. In the disclosed technical solutions, the water-to-olefins ratio is typically 1.5 or even higher because water vapor plays a crucial role in the reaction, and reducing the water-to-olefins ratio would pose a challenge to catalytic performance.
[0004] The selective oxidation of propylene to acrolein is a strongly exothermic reaction, requiring timely removal of the heat of reaction by water vapor to control the temperature rise. A decrease in the water-to-propylene ratio (water-to-olefin ratio) leads to an increase in bed temperature and intensifies the reaction, resulting in a higher yield of the deep oxidation product, COx. Furthermore, water vapor and the target product, acrolein, compete for adsorption on the catalyst surface; a reduced water vapor ratio prevents timely desorption of acrolein, also contributing to an increased COx yield. In addition, water vapor is a crucial source of lattice oxygen in the catalyst during the selective oxidation of propylene to acrolein. If the water-to-olefin ratio decreases and lattice oxygen cannot be replenished in time, propylene is more likely to undergo non-selective oxidation to directly generate COx. Therefore, under low water-to-olefin ratio conditions, side reactions are typically exacerbated, catalyst selectivity decreases, and the COx-generating side reactions release a large amount of heat, causing the catalyst bed temperature to exceed the warning level.
[0005] Therefore, developing a catalyst specifically designed for low water-to-olefin ratio conditions is very promising. Summary of the Invention
[0006] The purpose of this invention is to provide a catalyst for the oxidation of propylene to acrolein under low water-to-olefin ratio conditions. This catalyst reduces the proportion of water vapor in the feedstock, allowing subsequent separation processes to utilize crystallization instead of azeotropic distillation, thus lowering separation costs. The catalyst employs elemental additives to reduce the yield of the deep oxidation product COx, utilizes a coating molding process with the addition of a diluent to ensure the catalyst's thermal conductivity, and uses a molding structure aid combined with a curing process to ensure the strength of the spherical catalyst after the introduction of the diluent. This results in a highly selective, high-strength spherical catalyst product suitable for low water-to-olefin ratio conditions.
[0007] The technical solution adopted in this invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a catalyst applicable under low water-to-olefin ratio conditions, comprising the following steps:
[0009] S1. Under heating conditions, molybdenum source and source A are added to deionized water to obtain material I. Iron source, cobalt source, nickel source and source B are added to deionized water to obtain material II. Bismuth source is added to nitric acid-acidified deionized water to obtain material III. Material II and material III are mixed and then added dropwise to material I to obtain precursor slurry.
[0010] S2. Add phosphoric acid to the precursor slurry, adjust the pH value, and age it by stirring at a constant temperature;
[0011] S3. The aged precursor slurry is dried, pulverized, and pre-calcined to obtain pre-calcined powder;
[0012] S4. After mixing the pre-calcined powder with diluent and structural aid, spray the binder aqueous solution in a rotary drum granulator to coat the mixed powder onto a spherical carrier to obtain a spherical catalyst. After static curing, the catalyst is obtained after calcination.
[0013] In a preferred embodiment, the molybdenum source, iron source, cobalt source, nickel source, and bismuth source are ammonium salts or nitrates, and source A and source B are nitrates.
[0014] In a preferred embodiment, the total concentration of the binder in the aqueous binder solution is 20-40%; the binder is glycerol and cellulose; the cellulose is selected from methylcellulose, ethylcellulose, cellulose acetate, carboxymethylcellulose or crystalline cellulose.
[0015] As a preferred embodiment, S2 specifically includes: adding phosphoric acid to the precursor slurry, adjusting the pH to 2.5 using ammonia water, and aging at a constant temperature with stirring for 1 hour.
[0016] In a preferred embodiment, the pre-baking temperature in S3 is 350-450℃, and the pre-baking time is 2-10 hours in an air atmosphere. Preferably, the pre-baking time is 6 hours at 400℃ in an air atmosphere.
[0017] The slurry drying method in S3 is conventional concentration drying or spray drying. The purpose of pre-calcination is to remove residual moisture and organic matter such as ammonium nitrate from the catalyst powder, thereby improving the stability of the powder's physicochemical properties. Air needs to be introduced during pre-calcination.
[0018] In a preferred embodiment, the mass of the diluent is 20% to 50% of the mass of the pre-calcined powder.
[0019] In a preferred embodiment, the diluent is one of silicon powder, silicon dioxide powder, and silicon carbide powder.
[0020] In a preferred embodiment, the structural additive is one of Al2O3 whiskers, SiC whiskers, and mullite whiskers.
[0021] In a preferred embodiment, the mass of the structural additive is 2% to 6% of the mass of the diluent.
[0022] In a preferred embodiment, the static curing in S4 is carried out in a tube furnace.
[0023] In a preferred embodiment, the curing temperature is room temperature and the curing time is 8~20h.
[0024] In a preferred embodiment, air is introduced during the curing process at a flow rate of 0-5 mL / min. -1 ·(g cat) -1 .
[0025] The roasting in S5 is a conventional roasting method, carried out in a muffle furnace. As a preferred embodiment, the roasting temperature is 480~520℃.
[0026] In the technical solution of this invention, an active powder formulation was developed to make the catalyst suitable for low water-to-olefin ratio conditions. To address the problem of reduced lattice oxygen sources leading to non-selective oxidation reactions and COx generation after a lower water-to-olefin ratio, this invention introduces promoters such as tellurium, cerium, samarium, and zirconium into the formulation. These promoters can regulate the surface and bulk structure of the catalyst, improving the replenishment and migration capabilities of lattice oxygen. To address the difficulty in desorbing and deeply oxidizing acrolein to COx after a lower water-to-olefin ratio, this invention introduces phosphorus into the formulation. This improves the charge distribution on the catalyst surface and promotes acrolein desorption. Considering that introducing phosphoric acid would affect the catalyst's acidity or alkalinity, ammonia was used to adjust the pH value after adding phosphoric acid.
[0027] In the technical solution of this invention, a spherical catalyst formulation was developed to make the catalyst suitable for low water-to-olefin ratio conditions. To meet the higher requirements for the thermal conductivity of the catalyst after the water-to-olefin ratio is reduced, this invention first uses a coating molding process to enhance the heat dissipation capability by utilizing the thermal conductivity of the α-Al2O3 support, and adds a diluent to further enhance the heat dissipation capability and inhibit deep reactions.
[0028] Compared to active powder, diluents have more stable physicochemical properties but lack adhesiveness. Therefore, adding diluents in the coating molding process poses a challenge to the strength of spherical catalysts, making them prone to pulverization and breakage, and easily clogging reaction tubes or even rendering them unusable during production. To address this issue, the present invention develops a coating molding process. First, mullite whiskers and other types of whiskers are introduced into the molding formula as structural aids. Their fibrous structure provides support and improves the strength of the catalyst. The amount of structural aid added depends on the whisker length and the diluent content. After molding, the mixture is allowed to stand and cure, allowing the binder to function and fully bond the active powder and diluent together, while simultaneously allowing the moisture introduced during molding to evaporate slowly.
[0029] Secondly, this invention provides a catalyst applicable under low water-to-olefin ratio conditions, obtained by the above-described preparation method. It includes a support and an active powder supported on the support, wherein the active powder has the general formula Mo. 12 Bi a Co b Ni c Fe d A e B f P g O xWhere A is at least one of potassium, rubidium, and cesium, B is one of cerium, samarium, zirconium, and praseodymium, and P is phosphorus; a = 0.6~2, b = 5~7, c = 1.5~4, d = 0.6~2.5, and x is determined by the values of other elements.
[0030] In a preferred embodiment, the value of e in the general formula of the active powder is 0.05~0.3, preferably 0.15~0.25.
[0031] In a preferred embodiment, the value of f in the general formula of the active powder is 0.2 to 0.7, preferably 0.3 to 0.5.
[0032] In a preferred embodiment, the value of g in the general formula of active powder is 0.01~0.2, preferably 0.05~0.15.
[0033] Thirdly, the present invention provides an application of the above-mentioned catalyst under low water-to-olefin ratio conditions, in the two-step oxidation process of propylene to prepare acrylic acid, for the selective oxidation of propylene to prepare acrolein.
[0034] This catalyst can reduce the proportion of water vapor in the feedstock, allowing subsequent separation processes to use crystallization separation instead of azeotropic distillation.
[0035] Fourthly, the present invention provides a method for the selective oxidation of propylene to prepare acrolein, wherein the reaction process uses the catalyst described above.
[0036] In a preferred embodiment, the reaction gas feedstock is propylene, air, water vapor, or nitrogen.
[0037] In a preferred embodiment, the volumetric flow rate ratio of propylene to water vapor is 1:0.2 to 1:0.5, preferably 1:0.3 to 1:0.4.
[0038] In a preferred embodiment, the volumetric flow rate ratio of propylene to air is 1:8 to 1:10, preferably 1:8.5 to 1:9.
[0039] In a preferred embodiment, the volumetric flow rate ratio of propylene to nitrogen is 1:3 to 1:5.
[0040] In a preferred embodiment, the propylene space velocity is 70-100 h⁻¹. -1 .
[0041] As a preferred embodiment, the reaction temperature is 310~330℃.
[0042] In a preferred embodiment, when the propylene conversion rate is greater than 98.5%, the hot spot temperature of the catalyst bed is lower than 410°C.
[0043] In the technical solution of this invention, to meet the requirements of crystallization separation, the water-to-olefin ratio in the raw material is below 0.5. Water vapor is a partial source of lattice oxygen; therefore, after reducing the water-to-olefin ratio, the air ratio needs to be appropriately increased. Simultaneously, water vapor has excellent heat dissipation capabilities, so the nitrogen ratio also needs to be increased to control the bed temperature. The selective oxidation of propylene to acrolein is a strongly exothermic reaction. In actual production, strict control of the bed temperature is necessary to avoid overheating that could damage the catalyst or even cause an explosion. After reducing the water-to-olefin ratio, the hot spot temperature of the catalyst bed will significantly increase. In industrial production plants, once the bed temperature exceeds 410°C, operators need to reduce the reaction load or even cut off the feed to ensure safety, affecting production. This invention evaluates catalyst performance in a small-scale pilot plant. Through the development of the catalyst formulation and the control of the feed ratio, it is possible to maintain the hot spot temperature below 410°C while ensuring catalyst activity (propylene conversion greater than 98.5%), meeting the needs of industrial production.
[0044] Compared with the prior art, the present invention has the following advantages:
[0045] 1. This invention, through the development of spherical catalyst active powder formulation, overall formulation, and coating molding process, has obtained a highly selective and high-strength spherical catalyst product suitable for low water-to-olefin ratio conditions. Combined with the control of the feed ratio, the catalyst exhibits excellent performance under low water-to-olefin ratio conditions, with low bed hot spot temperature, meeting the requirements of industrial use. Among them, Examples 1 to 8 can all achieve a total yield of over 93% of acrolein and acrylic acid at a water-to-olefin ratio of 0.3, with hot spot temperatures all below 410℃ and wear resistance all meeting the requirements.
[0046] 2. After the water-to-olefin ratio is reduced, the crystallization separation process can be used to replace the azeotropic distillation process in the product refining section. This results in a shorter equipment chain, lower energy consumption, and less environmental pressure, which can bring significant economic and social benefits to acrylic acid production. Attached Figure Description
[0047] Figure 1 The NH3-TPD spectra of Examples 1, 2 and Comparative Example 1 of this invention are shown below;
[0048] Figure 2 The TPRO spectra of Examples 1, 3, 4, Comparative Example 2, and Comparative Example 3 of the present invention are shown below.
[0049] Figure 3 These are exterior photographs of Embodiment 1 and Comparative Examples 9-13 of the present invention. Detailed Implementation
[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0051] Unless otherwise specified in the examples and comparative examples, the conditions were performed under standard conditions or as recommended by the manufacturer. All reagents and instruments used were commercially available products unless otherwise specified.
[0052] Example 1:
[0053] A catalyst for use under low water-to-olefin ratio conditions includes a support and an active powder supported on the support, wherein the active powder has the general formula Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Sm 0.4 P 0.1 O x The preparation method is as follows, according to the parts by weight:
[0054] S1. At 80℃ and under continuous stirring, 50.00 parts of ammonium molybdate tetrahydrate, 0.2386 parts of potassium nitrate, and 0.2300 parts of cesium nitrate were added to 150 parts of deionized water to obtain material I. 39.84 parts of cobalt nitrate hexahydrate, 19.22 parts of nickel nitrate hexahydrate, 12.39 parts of ferric nitrate nonahydrate, and 4.20 parts of samarium nitrate hexahydrate were added to 50 parts of deionized water to obtain material II. 17.17 parts of bismuth nitrate pentahydrate were added to 10 parts of 65% nitric acid-acidified deionized water (1 part of 65% nitric acid and 3 parts of deionized water were mixed) to obtain material III. Material II and material III were mixed and added to material I to obtain the precursor slurry.
[0055] S2. Slowly add 0.2721 parts of 85% phosphoric acid to the precursor slurry, adjust the pH to 2.5 with ammonia water, and age at a constant temperature with stirring for 1 hour;
[0056] S3. The slurry was dried in a 150℃ forced-air oven for 24 hours to obtain a block solid, which was then crushed and pre-calcined at 400℃ in air atmosphere for 6 hours to obtain a pre-calcined powder.
[0057] S4. Mix 70 parts of pre-calcined powder with 30 parts of SiC powder and 0.9 parts of mullite whiskers (the mass of the structural additive is 3% of the mass of the diluent). Place 100 parts of α-Al2O3 spherical supports with a diameter of 4.5 mm in a rotary drum granulator. While rotating, spray an aqueous solution of 30% glycerol and 3% cellulose acetate to coat the mixed powder onto the spherical supports, obtaining a spherical catalyst. Place the catalyst in a tube furnace and purge it at room temperature using 3 mL / min. -1 ·(g cat) -1 Allow air to stand and cure for 12 hours.
[0058] The product is obtained by calcining at 500℃ for 6 hours.
[0059] Example 2:
[0060] In Example 1, step S1, 0.2386 parts potassium nitrate and 0.2300 parts cesium nitrate were replaced with 0.4772 parts potassium nitrate, and the rest remained the same as in Example 1. The general formula of the active powder was Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.2 Sm 0.4 P 0.1 O x .
[0061] Example 3:
[0062] In Example 1, step S1, 4.20 parts of samarium nitrate hexahydrate were replaced with 4.10 parts of cerium nitrate hexahydrate, and the rest remained the same as in Example 1. The general formula of the active powder was Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Ce 0.4 P 0.1 O x .
[0063] Example 4:
[0064] In Example 1, step S1, 4.20 parts of samarium nitrate hexahydrate were replaced with 5.07 parts of zirconium nitrate pentahydrate, and the rest remained the same as in Example 1. The general formula of the active powder was Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Zr 0.5 P 0.1 Ox .
[0065] Example 5:
[0066] Replace 70 parts of pre-calcined powder, 30 parts of SiC powder, and 0.9 parts of mullite whiskers in step S4 of Example 1 with 60 parts of pre-calcined powder, 40 parts of SiO2 powder, and 1.2 parts of mullite whiskers (the mass of the structural aid is still 3% of the mass of the diluent), and the rest is the same as in Example 1.
[0067] Example 6:
[0068] Replace 0.9 parts of mullite whiskers in step S4 of Example 1 with 0.6 parts of SiC whiskers (the mass of the structural aid is 2% of the mass of the diluent), and the rest is the same as in Example 1.
[0069] Example 7:
[0070] Replace 0.9 parts of mullite whiskers in step S4 of Example 1 with 1.5 parts of Al2O3 whiskers (the mass of the structural aid is 5% of the mass of the diluent), and the rest is the same as in Example 1.
[0071] Example 8:
[0072] During the static curing process in step S4, the spherical catalyst is sealed in a tube furnace at room temperature and in an air atmosphere for 12 hours, and the rest is the same as in Example 1.
[0073] Comparative Example 1:
[0074] In Example 1, step S1, 0.2386 parts potassium nitrate and 0.2300 parts cesium nitrate were replaced with 0.7159 parts potassium nitrate and 0.4600 parts cesium nitrate, respectively. The rest remained the same as in Example 1. The general formula of the active powder was Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.3 Cs 0.1 Sm 0. 4P 0.1 O x .
[0075] Comparative Example 2:
[0076] In Example 1, step S1 does not include 4.20 parts of samarium nitrate hexahydrate; the rest is the same as in Example 1. The general formula of its active powder is Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 P 0.1 Ox .
[0077] Comparative Example 3:
[0078] In Example 1, step S1, 4.20 parts of samarium nitrate hexahydrate were replaced with 8.40 parts of samarium nitrate hexahydrate, and the rest remained the same as in Example 1. The general formula of the active powder is Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Sm 0.8 P 0.1 O x .
[0079] Comparative Example 4:
[0080] In Example 1, step S2 does not involve adding 0.2721 parts of 85% phosphoric acid, but ammonia is still used to adjust the pH to 2.5. The rest of the steps are the same as in Example 1. The active powder has the general formula Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Sm 0.4 O x .
[0081] Comparative Example 5:
[0082] In Example 1, step S2, 0.2721 parts of 85% phosphoric acid were replaced with 0.8163 parts of 85% phosphoric acid, while the rest remained the same as in Example 1. The general formula of the active powder is Mo. 12 Bi 1.5 Co 5.8 Ni 2.8 Fe 1.3 K 0.1 Cs 0.05 Sm 0.4 P 0.3 O x .
[0083] Comparative Example 6:
[0084] Replace 70 parts of pre-calcined powder, 30 parts of SiC powder, and 0.9 parts of mullite whiskers in step S4 of Example 1 with 100 parts of pre-calcined powder, and the rest is the same as in Example 1.
[0085] Comparative Example 7:
[0086] Replace 70 parts of pre-calcined powder, 30 parts of SiC powder, and 0.9 parts of mullite whiskers in step S4 of Example 1 with 90 parts of pre-calcined powder, 10 parts of Si powder, and 0.3 parts of mullite whiskers (the mass of the structural additive is still 3% of the mass of the diluent), and the rest is the same as in Example 1.
[0087] Comparative Example 8:
[0088] Replace 70 parts of pre-calcined powder, 30 parts of SiC powder, and 0.9 parts of mullite whiskers in step S4 of Example 1 with 40 parts of pre-calcined powder, 60 parts of SiC powder, and 1.8 parts of mullite whiskers (the mass of the structural aid is still 3% of the mass of the diluent), and the rest is the same as in Example 1.
[0089] Comparative Example 9:
[0090] In Example 1, step S4 does not involve adding 0.9 parts of mullite whiskers; the rest is the same as in Example 1.
[0091] Comparative Example 10:
[0092] Replace 0.9 parts of mullite whiskers in step S4 of Example 1 with 2.4 parts of SiC whiskers (the mass of the structural aid is 8% of the mass of the diluent), and the rest is the same as in Example 1.
[0093] Comparative Example 11:
[0094] The temperature for static curing in step S4 of Example 1 was changed from room temperature to 80°C, and the rest was the same as in Example 1.
[0095] Comparative Example 12:
[0096] The static curing time in step S4 of Example 1 was changed from 12h to 2h, and the rest was the same as in Example 1.
[0097] Comparative Example 13:
[0098] The air flow rate during static curing in step S4 of Example 1 was reduced from 3 mL·min. -1 ·(g cat) -1 Change to 15 mL·min -1 ·(g cat) -1 The rest is the same as in Example 1.
[0099] Performance testing
[0100] 1. Catalyst characterization:
[0101] The acidity and alkalinity of Examples 1, 2, and Comparative Example 1 were tested using a chemisorption analyzer via ammonia-programmed temperature desorption (NH3-TPD). The test procedure was as follows: After the active powder on the spherical catalyst was peeled off using an abrasion tester, it was granulated into tablets of 20-40 mesh. 0.2 g of the granulated sample was weighed and heated at 30 mL·min. -1 At a He flow rate of 20 °C·min -1 The temperature was increased to 400°C at a certain rate for degassing and held for 60 min. Then, it was allowed to cool naturally to 50°C, and then heated at 20 mL / min. -1 A 10 vol% NH3 / He mixed gas was introduced at a flow rate of 60 min and maintained for 60 min, then switched to 30 mL·min. -1 The He flow rate was maintained at 60 min to purge physically adsorbed NH3. Finally, the temperature-programmed desorption curve was recorded at a rate of 10 °C·min. -1 The recorded temperature range is 50~400℃, such as Figure 1 As shown.
[0102] The lattice oxygen replenishment capacity of Examples 1, 3, 4, Comparative Example 2, and Comparative Example 3 was tested using a chemisorption analyzer via temperature programmed re-oxidation (TPRO). The test procedure was as follows: After the active powder on the spherical catalyst was removed using an abrasion tester, it was granulated into tablets to obtain 20-40 mesh particles. 0.2 g of the granulated sample was weighed and bubbled through a 10 mL·min filter at 320 °C. -1 Propylene was pretreated for 2 hours to consume the lattice oxygen on the catalyst, and then cooled to 50°C after purging with pure He. The gas flow rate was then switched to 30 mL∙min⁻¹. -1 10 vol% O2 / He, at 10 °C·min -1 The temperature was increased from 50℃ to 500℃ at a rate that allowed for the concentration of O2 (m / z=32) to be recorded by mass spectrometry. Figure 2 As shown.
[0103] The strength of all examples and comparative examples was tested on a rotary abrasion tester as follows: 100g of spherical catalyst was placed in a rotary drum and rotated at 25r / min for 10min. The mass of the detached active powder was weighed and divided by 100g to obtain the abrasion data, which is listed in Table 3.
[0104] 2. Catalyst performance evaluation:
[0105] The performance of selective oxidation of propylene to acrolein under low water-to-propylene ratio was tested in a small-scale pilot-scale fixed-bed reactor for the examples and comparative examples. The evaluation method is as follows: 200 mL of spherical catalyst and 200 mL of diluted spheres were thoroughly mixed and placed in a reaction tube. The small-scale pilot-scale fixed-bed reactor was heated by molten salt, and the temperature of the reaction tube was uniform. The reaction raw materials were propylene, air, water vapor and nitrogen. The reaction temperature was 310~330℃ and the reaction pressure was atmospheric pressure. The catalyst performance was analyzed by gas chromatography, and the data when the carbon balance was 95~105% were selected as valid data.
[0106] Application Example 1:
[0107] The catalyst of Example 1 was tested under different reaction conditions. The selection of reaction conditions when the catalyst of the present invention is used under low water-to-olefin ratio conditions is explained. The data are shown in Table 1 and Table 2.
[0108] Table 1 Example 1 at 80h -1 Propylene space velocity and catalytic performance under different feed ratios
[0109]
[0110] The selective oxidation of propylene to acrolein is the first step in the two-step oxidation process of propylene to produce acrylic acid. Therefore, this invention focuses more on the total yield of acrolein and acrylic acid than on the yield of acrolein. As shown in Table 1, as the water-to-olefin ratio gradually decreases from 1.5 to 0.2, the catalyst bed hotspot temperature gradually increases. This is due to the reduced heat removal capacity of the reaction system caused by the decrease in water vapor flow rate. However, the hotspot temperature in Example 1 remained below 410°C. The examples in this invention are more suitable for low water-to-olefin ratio conditions. Therefore, under the conventional conditions of a propylene:air:water vapor:nitrogen volumetric flow rate of 1:7.5:1.5:0, Example 1 requires a bed temperature of 330°C to achieve a propylene conversion of 98.6%, with a total yield of 92.6% for acrolein and acrylic acid.
[0111] When the volumetric flow rate of propylene: air: water vapor: nitrogen is 1: 7.7: 1: 2, and the water-propylene ratio is reduced to 1, nitrogen feed needs to be increased to compensate for the dilution and heat removal effect of water vapor. At this time, Example 1 can achieve a propylene conversion rate of 98.9% at 325°C and a total yield of 92.8%.
[0112] When the water-to-propylene ratio gradually decreased to 0.5, 0.4, and 0.3, a propylene conversion rate of over 99% could be achieved at 320℃. Under the condition of a water-to-propylene ratio of 0.3, when the air-to-propylene ratio increased from 8.0 to 8.5, the selectivity improved, and the overall yield increased from 92.5% to 93.0%. This is because both water vapor and air are sources of lattice oxygen; when the proportion of water vapor decreases, the proportion of air needs to be appropriately increased to compensate for the lack of lattice oxygen and improve reaction selectivity.
[0113] When the air-to-propylene ratio increased to 8.7, the selectivity further improved, and the overall yield increased to 93.3%. However, when the air-to-propylene ratio further increased to 9.5, the selectivity decreased, which was due to the higher oxygen concentration leading to a deeper degree of oxidation. When the water-to-propylene ratio decreased to 0.2, the bed temperature further decreased to 315℃, and the selectivity also decreased slightly, requiring an appropriate increase in the nitrogen ratio. When the nitrogen-to-propylene ratio increased from 4 to 5, the overall yield increased from 91.6% to 92.3%. When the nitrogen-to-propylene ratio further increased to 6, the feed gas linear velocity was too high, and the propylene could not fully contact the active sites, resulting in a decrease in performance.
[0114] Table 2. Catalytic performance of Example 1 at different space velocities with a propylene:air:water vapor:nitrogen ratio of 1:8.7:0.3:4.
[0115]
[0116] According to the results in Table 1, the total yield of acrolein and acrylic acid in Example 1 was highest when the volume flow ratio of propylene:air:water vapor:nitrogen was 1:8.7:0.3:4. Therefore, this feed ratio was selected, and the catalytic performance was tested at different space velocities, as shown in Table 2.
[0117] When the propylene space velocity is 70 h -1 At this time, with a low reaction load, a propylene conversion rate of 99.1% can be achieved at 315℃, with a total yield of 93.0%. This is achieved when the propylene space velocity is 80 h⁻¹. -1 90 h -1 At this time, the bed temperature needs to be raised to 320℃ to activate more reaction sites, of which 90h -1 The preferred propylene space velocity achieves a total yield of 93.6% for acrolein and acrylic acid. As the propylene space velocity increases, on the one hand, the bed temperature needs to be increased to ensure propylene conversion; on the other hand, the increased reaction load leads to increased heat release, thus significantly raising the hot spot temperature. When the propylene space velocity is 110 h⁻¹... -1 At that time, the catalyst selectivity decreased slightly, the overall yield dropped to 92.4%, and the hot spot temperature increased significantly to 408.6℃.
[0118] Application Example 2:
[0119] Based on the results of Application Example 1, the volumetric flow rate ratio of propylene:air:water vapor:nitrogen was selected as 1:8.7:0.3:4, and the propylene space velocity was selected as 90 h⁻¹. -1 The performance of the embodiments and comparative examples of this invention under low water-to-olefin ratio conditions was tested, and the performance data and wear data are listed in Table 3.
[0120] In publicly available technical solutions (patents CN112958103B and CN105195166A), the type and content of alkaline auxiliaries are typically around K 0.1. However, in this invention, the alkaline auxiliaries in Example 1 are K 0.1 and Cs 0.05, and in Example 2, K 0.2. This is because under low water-to-olefin ratio conditions, more acidic sites need to be neutralized to avoid non-selective oxidation reactions. The reaction performance of Examples 1 and 2 is similar, with the hot spot temperature of the K and Cs combination being lower. In Example 1, the alkaline auxiliaries are K 0.3 and Cs 0.1. At this point, the content of alkaline auxiliaries is too high, which not only neutralizes non-selective acidic sites but also covers selective oxidation sites, thus leading to an increase in COx yield. Figure 1 The NH3-TPD spectra of Examples 1, 2, and Comparative Example 1 are shown. Examples 1 and 2 have similar numbers of acidic sites, and therefore similar reaction performance. However, Comparative Example 1 has a significantly reduced number of acidic sites due to the addition of too much alkaline additive.
[0121] Examples 1, 3, and 4 respectively added Sm, Ce, and Zr as auxiliary metals to enhance the lattice oxygen replenishment capacity of the catalyst under low water-to-olefin ratio conditions. Examples 3 and 4 showed similar catalytic performance and excellent selectivity. As a control, Comparative Example 2 did not add these auxiliary metals. Not only did the bed temperature need to be increased to 325℃, but the overall yield was only 90.5%, and the COx yield was as high as 6.3%. This is because with a lower water-to-olefin ratio, not only is it necessary to appropriately increase the proportion of oxygen, but from the catalyst's perspective, the lattice oxygen replenishment capacity also needs to be improved. Otherwise, propylene is prone to non-selective oxidation to generate COx. Sm, Ce, and Zr are very effective auxiliary metals, but the appropriate amount must be selected. Comparative Example 3 added excessive Sm, which improved the activity, achieving a 99% conversion rate at 315℃, but the selectivity decreased compared to Example 1. This invention characterizes the lattice oxygen replenishment capacity of the catalyst through a programmed temperature-controlled re-oxidation experiment. Figure 2As shown, the peak temperature for lattice oxygen replenishment in Comparative Example 2 was 180.1℃. The peak temperatures in Examples 1, 3, and 4 were significantly reduced to 165.0℃, 168.7℃, and 169.3℃, respectively, indicating that lattice oxygen was easier to replenish and the oxygen consumption (i.e., the amount of lattice oxygen replenished) was also significantly increased. The peak temperature in Comparative Example 3 was further reduced to 161.3℃, and the peak area was also larger. However, for selective oxidation reactions, the consumption and replenishment rates of lattice oxygen need to be matched. Excessive lattice oxygen replenishment capacity can also lead to non-selective oxidation reactions.
[0122] To adapt to reaction conditions with a low water-to-propylene ratio, this invention adds phosphorus (P) to the active powder formulation to improve charge distribution, enabling rapid desorption of acrolein and preventing deep oxidation to COx. Compared to Example 1, Comparative Example 4, which did not add P, exhibited significant deep oxidation, with a COx yield as high as 8.1% and a total yield of only 88.7%. Comparative Example 5, which added excessive P, may have also inhibited propylene adsorption, resulting in a propylene conversion rate of only 98.2% at 330°C.
[0123] Under low water-to-olefin ratio conditions, the heat dissipation capacity of the reaction system decreases. Therefore, a diluent needs to be added to the spherical catalyst to improve its thermal conductivity. Example 1 used 30% SiC powder for dilution, and Example 5 used 40% SiO2 powder for dilution, both of which achieved good results. The catalyst selectivity was excellent, and the hot spot temperature was below 410℃. Comparative Example 6 did not add a diluent, and the reaction was significantly exothermic. Even after the bed temperature was reduced to 310℃, the hot spot temperature was still as high as 413.3℃, exceeding the warning temperature, and deep oxidation was severe, with a COx yield as high as 10.2%. Comparative Example 7 used 10% Si powder for dilution. Compared with Comparative Example 6, the Si powder had a dilution effect, and the hot spot temperature was reduced to 407.6℃. However, the dilution ratio was too low, and the COx yield was still as high as 8.7%. Comparative Example 8 used 60% SiC powder for dilution. The excessive dilution ratio resulted in an insufficient number of active sites, and the propylene conversion rate was only 97.2% when the bed temperature was 330℃.
[0124] In the technical solution of this invention, the wear index of the spherical catalyst is less than 5%, which meets the usage requirements; otherwise, it is prone to pulverization or breakage during handling and use. Adding a diluent to the spherical catalyst will lead to a decrease in strength and an increase in wear. Therefore, this invention improves the strength by adding various types of whiskers and using a curing process. Examples 1-5 and Comparative Examples 1-5 all used mullite whiskers (15-20 micrometers in length, added at 3% of the mass of the diluent) and a curing process. The catalyst wear was less than 5%. Comparative Example 6 did not add any diluent, and the wear was only 0.3% without the addition of structural aids, proving that adding diluent has a significant impact on wear. Comparative Example 7 added only 10% diluent, and the wear was only 1.1%. Comparative Example 8 added 60% diluent, and the wear was as high as 6.6%. In Example 6, the whiskers were replaced with 2% (by weight of diluent) SiC whiskers (50-80 micrometers in length). Because the whiskers were longer, the amount added could be reduced accordingly to achieve the desired effect. In Example 7, the whiskers were replaced with 5% (by weight of diluent) Al2O3 whiskers (1.5-5 micrometers in length). The whisker length was shortened, requiring an increase in the amount added accordingly. The performance and wear data of Examples 6 and 7 were excellent. Comparative Example 9, without the addition of structural additives, showed a wear rate as high as 15.7%, and its appearance showed obvious powdering and cracking compared to Example 1. Figure 3 As shown, Comparative Example 10 contained SiC whiskers with 8% (by mass) of diluent. The excessive addition of long whiskers resulted in an irregular, protruding shape, such as... Figure 3 As shown, the "protruding" portion is prone to wear in the abrasion test, resulting in a wear rate as high as 10.2%. This invention also utilizes a curing process to improve abrasion resistance. In Example 1, 3 mL / min was introduced into a tube furnace at room temperature. -1 ·(g cat) -1 In Example 8, the air was allowed to stand for 12 hours for curing. In Example 9, curing was performed in a sealed tube furnace with zero airflow. This change resulted in less moisture evaporation during curing, which evaporated rapidly during calcination, affecting catalyst strength and slightly increasing wear to 4.3%. However, the yield of the target product also slightly increased to 93.8%. Those skilled in the art can choose the appropriate method based on their specific needs. In Comparative Example 11, the curing temperature was increased to 80°C; in Comparative Example 12, the curing time was shortened to 2 hours; and in Comparative Example 13, the airflow rate during curing was increased to 15 mL / min. -1 ·(g cat) -1 All of the above changes led to unsatisfactory curing results, with wear exceeding 5%, and visible cracks appearing on the spherical catalyst. Figure 3 As shown. Comparative Examples 9-12 had abrasion levels exceeding 10%, making them extremely prone to powdering and breakage, and thus did not meet the requirements for industrial use. Therefore, their catalytic performance was not evaluated.
[0125] Table 3 Performance and attrition of acrolein catalyst under low water-to-olefin ratio conditions
[0126]
[0127] The above embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit it. Within the principles of the present invention, any person skilled in the art can modify or make equivalent substitutions to the described embodiments, and such modifications and variations should be considered to fall within the protection scope of the present invention.
Claims
1. A method for preparing a catalyst applicable under low water-to-olefin ratio conditions, characterized in that, Includes the following steps: S1. Under heating conditions, molybdenum source and source A are added to deionized water to obtain material I. Iron source, cobalt source, nickel source and source B are added to deionized water to obtain material II. Bismuth source is added to nitric acid-acidified deionized water to obtain material III. Material II and material III are mixed and then added dropwise to material I to obtain precursor slurry. S2. Add phosphoric acid to the precursor slurry to adjust the pH value, and age it by stirring at a constant temperature; S3. The aged precursor slurry is dried, pulverized, and pre-calcined to obtain pre-calcined powder; S4. The pre-calcined powder is mixed with diluent and structural aid to obtain a mixed powder. A spherical carrier is placed in a rotary drum granulator, and an aqueous binder solution is sprayed to coat the mixed powder onto the carrier to obtain a spherical catalyst. The catalyst is then allowed to stand and solidify. After calcination, the catalyst is obtained. The molybdenum source, iron source, cobalt source, nickel source, and bismuth source are ammonium salts or nitrates, and sources A and B are nitrates.
2. The preparation method according to claim 1, characterized in that, The total mass concentration of the binder in the aqueous binder solution is 20-40%; the binder is glycerol and cellulose; the cellulose is selected from methylcellulose, ethylcellulose, cellulose acetate, carboxymethylcellulose or crystalline cellulose.
3. The preparation method according to claim 1, characterized in that, The pre-baking temperature in S3 is 350-450℃, and the pre-baking time is 2-10 hours in air atmosphere.
4. The preparation method according to claim 1, characterized in that, The diluent is at least one of silicon powder, silicon dioxide powder, and silicon carbide powder, and the mass of the diluent is 20% to 50% of the mass of the pre-baked powder.
5. The preparation method according to claim 1, characterized in that, The structural additive is at least one of Al2O3 whiskers, SiC whiskers, and mullite whiskers, and the mass of the structural additive is 2% to 6% of the mass of the diluent.
6. The preparation method according to claim 1, characterized in that, The static curing described in step S4 is carried out in a tube furnace at room temperature for 8-20 hours, with air introduced during curing at a flow rate of 0-5 mL / min. -1 ·(g cat) -1 .
7. A catalyst for use under low water-to-olefin ratio conditions, characterized in that, The preparation method according to any one of claims 1-6 yields a product comprising a carrier and an active powder loaded on the carrier, wherein the active powder has the general formula Mo. 12 Bi a Co b Ni c Fe d A e B f P g O x Where A is at least one of potassium, rubidium, and cesium, B is one of cerium, samarium, zirconium, and praseodymium, and P is phosphorus; a = 0.6~2, b = 5~7, c = 1.5~4, d = 0.6~2.5, e is 0.05~0.3, f is 0.2~0.7, and g is 0.01~0.
2.
8. An application of the catalyst according to claim 7, characterized in that, The catalyst is used to selectively oxidize propylene to prepare acrolein. In the catalytic reaction, the volume flow ratio of propylene to water vapor is 1:0.2 to 1:0.
5.
9. The application according to claim 8, characterized in that, Propylene space velocity is 70~100h -1 The reaction temperature is 310~330℃. When the propylene conversion rate is greater than 98.5%, the hot spot temperature of the catalyst bed is lower than 410℃.
10. A method for the selective oxidation of propylene to prepare acrolein, characterized in that, Using the catalyst of claim 7, the reaction gas feedstock is propylene, air, water vapor, and nitrogen, the volume flow ratio of propylene to water vapor is 1:0.2 to 1:0.5, the volume flow ratio of propylene to air is 1:8 to 1:10, and the volume flow ratio of propylene to nitrogen is 1:3 to 1:5.
Citation Information
Patent Citations
Preparation method of catalyst for preparing acrolein through propylene oxidation at high airspeed
CN101850259B
Method for preparing acrolein catalyst by propylene oxidation
CN105195166A
Catalysts for the catalytic oxidation of propylene to acrolein and their preparation methods
CN112958103B